EKSPEKTASI GURU SEKOLAH DASAR TERHADAP PENGGUNAAN APLIKASI BERBASIS WEB DALAM PEMBELAJARAN DARING DI ERA PANDEMI - Linda Feni Haryati; Arif Widodo (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The media has a crucial role in online learning in the pandemic era. One of the media that teachers need in online learning is a web-based application. This study aimed to determine teacher expectations of the use of web-based applications in online learning. This study was survey research conducted at one of the public elementary schools in Kabupaten Lombok Barat. The survey was conducted on 15 primary school teachers. The results of the study indicated that teachers were not familiar with web-based applications to facilitate online learning. Only 20% of teachers were reliable with the use of web-based applications for learning. Most teachers expected to receive training related to the use of web-based applications. The application used was only limited to the WhatsApp Group. Teachers' ability to use other web-based applications was still limited. At least 80% of teachers felt that they needed special training in the use of web-based applications for the learning process and the evaluation of students' learning outcomes.